How bank competition influence liquidity creation - Roman Horvath; Jakub Seidler; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
This paper evaluates the effect of bank competition on liquidity creation by banks. Thus, we contribute to the literature on both bank competition and the determinants of liquidity creation by banks. To explore this relationship, we conduct dynamic GMM panel estimations on a dataset of Czech banks from 2002 to 2010. We find that enhanced competition reduces liquidity creation, a finding we observe under different specifications, including alternative measures of liquidity creation. We explain this finding in terms of the impact of increased bank competition on the financial fragility of banks, which leads banks to reduce their lending and deposit activities. The evidence suggests that pro-competitive policies in the banking industry can reduce liquidity provision by banks.
URN:NBN:fi:bof-201408072068
Keywords: G21; 330; bank competition; liquidity creation